Targeting Oxidative Injury and Cytokines' Activity in the Treatment with Anti‐Tumor Necrosis Factor‐α Antibody for Complex Regional Pain Syndrome 1. Issue 8 (21st January 2013) - Miclescu, Adriana A.; Nordquist, Lena; Hysing, Eva‐Britt; Butler, Stephen; Basu, Samar; Lind, Anne‐Li; Gordh, Torsten
Abstract Cytokines and oxygen free radicals have been implicated in the potential pathogenic development of complex regional pain syndrome (CRPS). We aimed to analyze the relationship between clinical status, circulating levels of cytokines, and markers of oxidative damage during the treatment with anti‐TNFα antibodies. The patient chosen for treatment had not had improvement through a number of conventional therapies and fulfilled the current diagnostic criteria for CRPS‐1. We investigated the clinical variables before and after systemic administration of 1.4 mg/kg anti‐TNFα antibody (infliximab), repeated after 1 month in a dose of 3 mg/kg. Blood samples were collected before and after anti‐TNFα antibodies administration, and plasma was analyzed for 8‐isoprostane‐prostaglandin F2α (8‐iso‐PGF2α, a marker of oxidative injury) and cytokines (TNF‐α, IL‐4, IL‐6, IL‐7, IL‐8, IL‐10, IL‐17A). Plasma concentrations of 8‐iso‐PGF2α were measured with radioimmunoassay (RIA), and the kinetics of cytokines were detected in plasma by antibody‐based proximity ligation (PLA). Pathologically high levels of 8‐iso‐PGF2α were found in the patient. Immediately after each administration of infliximab, the levels of 8‐iso‐PGF2α decreased. Although the patient showed an improvement of the cutaneous dystrophic symptoms and diminished pain associated with these lesions, the levels of circulating TNFα increased after the administration of anti‐TNFα antibodies. In a patient with CRPS‐1 treated with anti‐TNFα antibodies, we report increased levels of circulating TNFα and a temporary mitigation of oxidative stress as measured by plasma F2‐isoprostane. This case report provides evidence 2 supporting the indication of monitoring the oxidative stress biomarkers during treatment with anti‐TNFα antibodies in CRPS 1.